An international comparison of competency-based orthopaedic curricula and minimum operative experience - Review article. (October 2021) - Tahir, Muaaz; Rahman, Usama; Gulati, Aashish
Abstract: Introduction: Orthopaedic training has undergone considerable changes in the last few decades. Although structured training pathways exist in most countries, the requirements for completion of training are remarkably different. This review aims to assess key differences among orthopaedic curricula in selected high-income countries with well-established orthopaedic training programmes, focusing on their criteria for assessing technical competence prior to completion of training. Methods: Current orthopaedic training curricula published by the relevant accrediting bodies in the UK, USA, Canada, Australia, Germany and the European Union were reviewed. Data extracted included specified training duration, minimum or desirable operative experience requirements, methods and timing of in-training assessments. Results: The overall training duration ranged between 9 and 10 years in the UK and Australia, compared to 5–6 years in all other countries. While operative logbook was an essential component of formative and end-of-training reviews in all countries, minimum indicative numbers in index operations were a requirement only in the UK (minimum total required; 1800, index operations; 365) and USA (minimum total required; 1000, index operations; 455). On average, USA residents performed 1700 procedures compared to German residents performing 730 procedures before completion of training. Conclusion: There is a lack of robust data describing the operative experiences of orthopaedic trainees outside of the UK and USA. UK training is the longest among countries compared in this review and also sets the highest standards in minimum operative experience requirements. Based on the evidence available, surgeons exiting training and entering independent practice in the above countries are not trained to the same minimum standard. Highlights: Assessment of procedural competence in orthopaedic training varies across countries. A combination of logbook and performance-based assessment are used in most countries. Less is known about the operative experiences of trainees outside of the UK and USA. Surgeons entering independent practice in the studied 5 regions are not trained to the same minimum standard.